(untitled) (Journal of Civil Engineering Researchers, 2024)
Due to the damage that occurred in the unreinforced welded flange (WUF) connections during the 1994 Northridge earthquake, the use of reduced beam section (RBS) connections and subsequently the reduced web section (RWS) connections became common to prevent premature brittle failure in the welded connections. The RWS connections are created to provide a controlled weak point for the formation of a plastic hinge, which can prevent stress concentrations in the groove welds of the connection. This method, where the transfer of the plastic hinge is achieved by weakening the beam web and without the need to remove the concrete slab, is proposed as a suitable solution for the rehabilitation of connections. In this paper, the effect of different beam web weakening patterns on the seismic performance of the connection is investigated analytically and numerically. Seven beam web weakening designs were studied and compared with the uniform web slotting pattern, and the seismic behavior of the mentioned connections was simulated using the Abaqus software, and the effect of using each of them on the distribution of equivalent plastic strains and the moment-rotation curve was examined. The results showed that the appropriate beam web weakening pattern plays an effective role in reducing the plastic strain in the penetration weld of the direct beam-to-column connection and preventing their premature tearing and failure, so that one of the perforation designs studied can reduce the maximum equivalent plastic strain in the upper penetration weld of the direct beam-to-column connection by an average of 48% compared to the uniform web slotting pattern as the reference connection.